Rancang Bangun Sistem Pariwisata Buton Tengah Berbasis Web - satin la ruma; Olivia Kembuan; Made Krisnanda (JOINTER : Journal of Informatics Engineering, 2022)
Central Buton is an area located in the Buton archipelago, Southeast Sulawesi which is a former heritage area of the Sultanate of Buton where the area has many natural and cultural tourist charms that must be preserved. This study aims to design and implement web-based tourism in Buton Tengah. The method used in the development of this application is Waterfall in which there are five namely Analysis, Design, Coding, Testing, and Implementation of Maintenance Programs, with the PHP programming language and Sublime Text 3. The result of the research is that the Central Buton Tourism system is website-based and has a service function, namely the function of providing tourist information, booking tickets, so that the sales system can be improved for the better. Testing this system using the Black Box testing method, so that it is able to answer and show that the system created is in accordance with the objectives of the researcher and is able to meet user needs.